2014
DOI: 10.5012/bkcs.2014.35.11.3294
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Control of Autler-Townes Splitting in Photoelectron Spectroscopy: The Effect of Laser Intensity and Laser Envelope

Abstract: We theoretically investigated the coherent control of Autler-Townes splitting in photoelectron spectroscopy of K 2 molecule within an ultrafast laser pulse by solving the time-dependent Schrodinger equation using a quantum wave packet method. It was theoretically shown that we can manipulate the splitting of photoelectron spectroscopy by altering the laser intensity. Furthermore, it was found that the percentages of each peak in photoelectron spectroscopy can be controlled by changing the envelope of the laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Laser parameters, such as laser intensity [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], laser wavelength [4][5][6][7][8][12][13][14][15][16]18], pulse width [1][2][3][7][8][9][10]18,19], pulse envelope [4,5], and delay time [10][11][12][13][14][15][16][17] can be used for controlling the excitation, ionization and dissociation processes of molecules, and have been studied in multi-level molecular systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Laser parameters, such as laser intensity [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], laser wavelength [4][5][6][7][8][12][13][14][15][16]18], pulse width [1][2][3][7][8][9][10]18,19], pulse envelope [4,5], and delay time [10][11][12][13][14][15][16][17] can be used for controlling the excitation, ionization and dissociation processes of molecules, and have been studied in multi-level molecular systems.…”
Section: Introductionmentioning
confidence: 99%
“…Christoph et al [1] and Hu et al [2,3] studied the effect of laser intensity and pulse width on photoelectron spectra of four-level Na 2 /Li 2 , and suggested that there is no Autler-Townes (AT) triple splitting for weaker pump laser intensity or shorter pulse width, longer pulse width can induce symmetric AT triple splitting. Yao et al [4], Qin et al [5] and Guo et al [6] suggested the laser intensity, pulse width and laser wavelength affect the asymmetry of AT splitting, and can control the selective population of dresses states of four-level K 2 . Sun et al [7] and Yuan et al [8] studied the effect of laser intensity, pulse width, molecular rotation and molecular alignment on photoelectron spectra of three-level Na 2 , and suggested that there is no AT double splitting for weaker laser intensity or shorter pulse width, longer pulse width can induce symmetric AT double splitting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autler-Townes (AT) splitting occurs due to nonlinear interactions between light and matter driven by one or more strong variable radiation fields [1]. AT splitting is found to be sensitive to laser intensity [2−18], laser wavelength [2−6, 10, 14−17], pulse width [11], pulse envelope [13,17,18], and time delay [7][8][9]14]. It has been studied theoretically and experimentally in multi-level atomic/molecular system of various configurations.…”
Section: Introductionmentioning
confidence: 99%